1977
DOI: 10.1093/ajcn/30.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Body size and work output

Abstract: The relationship between work output and anthropometric, biochemical, and socioeconomic varables was studied in 57 male industrial workers engaged in the production of detonator fuses. These workers were studied for 3 months and their daily work output was carefully measured. Work output was measured in terms of the number of fuses produced per day. Clinical and biochemical examination indicated that their current nutritional status was adequate. Among the parameters studied only body weight, height, and lean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 1 publication
1
26
0
4
Order By: Relevance
“…Since VO 2 max is related to body weight and lean body mass, total daily output and productivity of the undernourished adult is likely to be lower than that of the well-nourished. This is true even in work in industrial situations of less intensity than manual labour, where productivity has been shown to be related to body weight and LBM (Satyanarayana et al, 1977).…”
Section: Adaptations To Low Energy Intakes Ps Shettymentioning
confidence: 98%
“…Since VO 2 max is related to body weight and lean body mass, total daily output and productivity of the undernourished adult is likely to be lower than that of the well-nourished. This is true even in work in industrial situations of less intensity than manual labour, where productivity has been shown to be related to body weight and LBM (Satyanarayana et al, 1977).…”
Section: Adaptations To Low Energy Intakes Ps Shettymentioning
confidence: 98%
“…Measures of body size correlated positively with productivity in cane cutters in East Africa and Colombia (Davies, 1973;Spurr et al, 1975Spurr et al, , 1977Spurr, 1983Spurr, , 1988, and in nutritionally normal factory workers in India (Satyanarayana et al, 1977), but not in lumberjacks (Hansson, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Outstanding Indian contributions bearing on the question of "adaptation" to chronic energy deficit, and on the functional significance of small body size, are those of Shetty (59) and Satyanarayana et al (55)(56)(57)(58). These authors emphasize the point that while small body size and behavioral alterations in work patterns arising from chronic energy deficit may facilitate survival under marginal living conditions, they cannot be viewed as beneficial satisfactory adaptive responses consistent with optimal levels of productivity GOPALAN and quality of life.…”
Section: Misuse Of the Term Adaptationmentioning
confidence: 99%
“…These authors emphasize the point that while small body size and behavioral alterations in work patterns arising from chronic energy deficit may facilitate survival under marginal living conditions, they cannot be viewed as beneficial satisfactory adaptive responses consistent with optimal levels of productivity GOPALAN and quality of life. Physical activity, especially with respect to moderate and strenuous work, is compromised in subjects with low body weight and poor muscle mass (55,56), and there is no convincing evidence of increased metabolic efficiency with respect to energy handling by the residual active tissues of the body in chronically energy deficient small-sized individuals (59).…”
Section: Misuse Of the Term Adaptationmentioning
confidence: 99%